Terapia anti-retroviral em indivíduos vivendo com HIV/Aids, Belo Horizonte, 2001 - 2003: o desafio da adesão - Palmira de Fatima Bonolo (2005)
It is consensual for health services that adherence to antiretroviral therapy (ARVT) is a challenge. Antiretroviral (ARV) drugs brought excellent clinical results, but these benefits are dependent directly on treatment adherence. Several studies show that factors related to healthservices, to therapeutic regimen and patients, and to socio-cultural and environments, many of them prone to intervention and control, are associated with non-adherence. The objectives of this thesis were to assess the incidence and factors associated to non-adherence and todescribe vulnerability profiles among patients initiaing antiretroviral therapy, at two public referral centers for HIV/AIDS, in Belo Horizonte (MG), from 2001 to 2003. Patients receiving their first ARV prescription were recruited from 2001 to 2002 (baseline interview) and followed up to 2003 (follow-up visits at 1st, 4st, and 7st months). Socio-demographic andbehavioral characteristics were collected during baseline interview and non-adherence data from follow-up visits. The adherence measurement was self-reported (standardized interview), defined as the number of prescribed doses for each ARV, during three days prior to follow-up visits (= 95%). The magnitude of the association among selected exposurevariables, including the vulnerability profiles generated, and the first episode of nonadherence was estimated by relative hazard (RH) with 95% of confidence interval (CI), obtained from Coxs proportional model, with level of significance of 0.05. Vulnerability profiles were described by Grade of Membership (GoM) analysis. The studied population showed socio-demographic characteristics (lower income and education) similar to the current trend of AIDS epidemic in Brazil. Three pure or extreme profiles were defined (higher, medium and lower vulnerability). In general, the higher vulnerability pure profile was the only one to show a higher probability of patients to use illicit drugs, alcohol and tobacco, andto report sex among men. The cumulative incidence of non-adherence was 36.9% and the incidence rate was 0.21/100 person-days. Unemployment (RH=2.17; p=0.011), alcohol use (RH=2.27; p<0.001), use of more than one health service (RH=0.54; p=0.002), number ofpills per day (RH=2.04; p=0.02), self-report of three or more adverse reactions (RH=1.64; p=0.017), switch in antiretroviral regimen (RH=2.72; p<0.001) and a longer time between HIV test result and the first antiretroviral prescription (RH=2.27; p<0.001) and the higher vulnerability profile (RH=1.84; p=0.021) were associated with an increased risk of nonadherence. The incidence of non-adherence was high considering the beginning of antiretroviral therapy. Factors associated with the first episode of non-adherence were related to behavior and vulnerability, clinical and health service utilization characteristics. It should be noted that strategies of early interventions need to be developed, even before starting ARV treatment. The implementation of feasible indicators to assess adherence an ongoing basis, should be one of the main goals of the programs of universal ARV distribution such in Brazil. This may help to prevent and minimize future occurrence of drugs resistance to HIV and to have better treatment outcomes. It is imperative that strategies to increment adherence to antiretroviral therapy and to effectively reduce risk behavior be developed simultaneously. Safe practices counseling should be part of an integral clinical care. From the programmatic point of view, patients under ARV treatment will certainly benefice from access to an integral care with emphasis in promotion and prevention.